Total systems study on D.A.P. Pipes Manufacturing - Cano, Gellie Anne Mae; Merino, Jecelyn Ana; Odevilas, Glo Ann; Reyes, Princess Emma
DAP Pipes Manufacturing, owned by David. A Pau, produces concrete pipes for construction of waterways and auxiliary purposes. The company stated that they have an estimated backorder quantity around 7100 pipes per year, which is 25% of their total pipes produced per year. The DMAIC methodology is used to addressing the problem of the company. The goal is to reduce the backorders to 5% of the total pipes produced. The define phase stated the two possible causes of the amount of backorder quantity: the defective products and the orders rejected because they cannot produce the pipes in the time the customers need them. In the Measure phase, it was seen that the contribution of defective products to the backorders are small compared tothe unmeasured amount of rejected orders. In the analyze phase, it was found that the space is not used efficiently and there are no standard procedures. Areas for improvement were identified and several alternatives were generated. In the Improvement phase, validation of recommended changes in layout to address the problems verified in the Analyze phase were provided along with the new layout. The Control phase contained a plan on how implement the proposed improvements in three-year time frame.